Regional Volumetric Differences Based on Structural MRI in Children With Two Subtypes of ADHD and Controls. (October 2017) - Semrud-Clikeman, Margaret; Fine, Jodene Goldenring; Bledsoe, Jesse; Zhu, David C.
Objective: The purpose of this study was to compare groups of children with two subtypes of ADHD and controls on selected regions using volumetric magnetic resonance imaging (MRI) measures. Children with ADHD were expected to have smaller volumes of the anterior cingulate cortex (ACC) and caudate. Parent behavioral rating measures of hyperactivity were predicted to relate to the volume of the caudate and attention with the ACC.Method: There were a total of 74 children in the final sample (27 controls, 25 ADHD:Combined type [ADHD:C], 22 ADHD:Inattentive type [ADHD:I]).Results: Findings indicated that the ADHD:C group had bilaterally smaller volumes of the caudate and ACC compared with the other two groups. In addition, parent ratings of attention and hyperactivity significantly predicted the right volume of the ACC, whereas hyperactivity ratings predicted the volume of the right caudate. Analysis of the ADHD groups without the control confirmed these findings.Conclusion: These findings indicate that different structures are related to the ADHD subtypes and suggest that they may be different phenotypes.